2016
DOI: 10.1016/j.jvs.2014.10.103
|View full text |Cite
|
Sign up to set email alerts
|

Cilostazol improves high glucose-induced impaired angiogenesis in human endothelial progenitor cells and vascular endothelial cells as well as enhances vasculoangiogenesis in hyperglycemic mice mediated by the adenosine monophosphate-activated protein kinase pathway

Abstract: Cilostazol prevents HG-induced endothelial dysfunction in EPCs and HUVECs and enhances angiogenesis in hyperglycemic mice by interactions with a broad signaling network, including activation of AMPK/ACC and probably cAMP/PKA pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(54 citation statements)
references
References 37 publications
3
51
0
Order By: Relevance
“…Therefore, the protective eff ect of cilostazol on oxidative stress and systemic cytokines release, which has been described in other studies, could benefi t such patients [31]. Finally, experimental data have shown that cilostazol seems to promote angiogenesis in both endothelial progenitor cells and vascular endothelial cells as well [32].…”
Section: At 28 Daysmentioning
confidence: 77%
“…Therefore, the protective eff ect of cilostazol on oxidative stress and systemic cytokines release, which has been described in other studies, could benefi t such patients [31]. Finally, experimental data have shown that cilostazol seems to promote angiogenesis in both endothelial progenitor cells and vascular endothelial cells as well [32].…”
Section: At 28 Daysmentioning
confidence: 77%
“…However whether cilostazol could be used as a potential drug to target DCs warrants further study. Some reports have shown that the effect of cilostazol is associated with the activation of the AMPK pathway, and this effect has been validated in various models [20,21,24,25]. Furthermore, AMPK has been suggested to play an important role in TLRs-induced IL-23 production [26].…”
Section: Discussionmentioning
confidence: 91%
“…3, IL23A promoter activity was * P < 0.05 vs. zymosan alone, ** P < 0.01 vs. zymosan alone, # P < 0.05 vs. cilostazol plus zymosan treatment. [20,21]. Thus, we aimed to clarify whether the inhibitory effect of cilostazol on IL-23 production by mo-DCs was mediated by AMPK by treating cells with an AMPK agonist (A-769662) and an AMPK antagonist (Compound C).…”
Section: Cilostazol Inhibited Myd88-induced Il23a Transcriptional Actmentioning
confidence: 99%
“…Cilostazol, a selective phosphodiesterase 3 inhibitor, is a commercially available drug that provides antiplatelet and vasodilatory effects mediated by an increase in intracellular cyclic adenosine monophosphate levels [4, 12, 13] and is prescribed to patients with peripheral artery disease only with intermittent claudication. However, there is still a lack of evidence supporting the benefits of this compound in CLI.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is still a lack of evidence supporting the benefits of this compound in CLI. Notably, cilostazol could provide additional cellular and proangiogenic effects, including protection of ECs from apoptosis [4, 12, 14], stimulation of the release of angiogenic factors [4, 15], and improved endothelial function of ECs [4, 12], thereby potentially enhancing angiogenesis [4, 12, 16]. However, the effects of cilostazol on the functions of human early EPCs and its potential mechanisms related to SDF-1 α /CXCR4 pathway are not well understood.…”
Section: Introductionmentioning
confidence: 99%